2007
DOI: 10.1086/509822
|View full text |Cite
|
Sign up to set email alerts
|

Ferrophilic Characteristics ofVibrio vulnificusand Potential Usefulness of Iron Chelation Therapy

Abstract: We determined the ferrophilic characteristics of Vibrio vulnificus to evaluate the potential usefulness of iron chelation therapy for the prevention of V. vulnificus infection. Readily available non-transferrin-bound iron (NTBI) is required for the initiation of V. vulnificus growth under in vitro iron-limited conditions and human ex vivo conditions. NTBI aided efficient transferrin-bound iron (TBI) use by V. vulnificus, and the vulnibactin-mediated iron-uptake system was expressed after bacterial growth had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…1 cell of V. vulnificus. Studies by Kim et al (7) concluded that V. vulnificus requires high levels of readily available non-transferrin-bound iron for the initiation of growth. V. vulnificus is known to produce two classes of iron-scavenging siderophores, catechol and hydroxymate, which allow for the use of transferrin-bound iron (7,11,13,19,20).…”
mentioning
confidence: 99%
“…1 cell of V. vulnificus. Studies by Kim et al (7) concluded that V. vulnificus requires high levels of readily available non-transferrin-bound iron for the initiation of growth. V. vulnificus is known to produce two classes of iron-scavenging siderophores, catechol and hydroxymate, which allow for the use of transferrin-bound iron (7,11,13,19,20).…”
mentioning
confidence: 99%
“…Apart from siderophore-mediated iron uptake, V. vulnificus utilizes non-transferrin-bound iron through a heme receptor, HupA (92). It has been suggested that non-transferrin-bound iron is required for initiation of V. vulnificus growth; therefore, HupA may be necessary for initial growth once the organism enters the host (60,92).…”
Section: Iron Acquisitionmentioning
confidence: 99%
“…More recently, Kim et al (23) showed the involvement of two nonribosomal peptide synthetases in the biosynthesis of vulnibactin. V. vulnificus can grow in human serum only with transferrin at high iron saturation (6); however, Kim et al (22) showed that nontransferrin-bound iron is required for the initiation of V. vulnificus growth. It is customary to use iron-overloaded mice in virulence studies with V. vulnificus to mimic the conditions found in susceptible individuals.…”
mentioning
confidence: 99%